A new analytical model for predicting the thermal oxidation kinetics of composite organic m atrices. Application to diamine cross-linked epoxy. (April 2021) - COLIN, Xavier; ESSATBI, Fatima; DELOZANNE, Justine; MOREAU, Gurvan
Highlights: A new analytical kinetic model is proposed for the thermal oxidation of organic matrix composites. Its reliability is successfully checked numerically. It is used to accurately identity the oxidation behavior of two epoxy-diamine matrices. It is used to determine the accelerated aging conditions perfectly representative of the natural aging. Abstract: The system of differential equations derived from the so-called "closed-loop" mechanistic scheme was solved analytically by applying realistic proportionality assumptions between the different concentrations of reactive species during the entire course of the thermal oxidation. This new method of analytical resolution allowed obtaining a sounder kinetic model accurately describing the three first stages of the thermal oxidation kinetics: the induction period, the auto-acceleration of the oxidation kinetics at the end of the induction period, and the steady-state regime. This kinetic model was used to identify the thermal oxidation behavior at 120 and 150°C in a large range of oxygen partial pressures (typically between 0.21 and 10 bars) of two epoxy-diamine (EPO-DA) matrices. In addition, the kinetic model was used to determine the accelerated aging conditions representative of the cruising flight of a commercial airliner. It was found that the oxygen partial pressure must be increased much more than the temperature to avoid any deformation of the structural degradation state in the two EPO-DA matrices, thus leading to the definition of extreme environmental conditions very difficult to access in practice.